THE EFFECT OF WIDE PUSH-UP EXERCISE AND NARROW PUSH-UP EXERCISE AGAINST STRENGTH, POWER, AND ENDURANCE - Nasiruddin Tamimi; Edy Mintarto; Nining Widya K. (Program Pascasarjana Universitas Negeri Jakarta, 2017)
This study aims to improve the level of physical condition, so it can be known and become an evaluation for the sport that achieves a better achievement later. The application of exercises used to improve physical condition is through wide push-ups and narrow push-ups in students of XI IPA in SMA N 1 Sumberrejo Bojonegoro. The type of research used in this study is quantitative with quasi experimental methods (Quasi Experiment). The design used to group research subjects is Matching-Only Design. In this design there are three groups, namely wide push-up exercise group, narrow push-up exercise group, and one control group. Furthermore, the three groups were given a pretest to determine the initial state is there any difference between the experimental group and the control group. After 8 weeks of practice with frequency 3 times a week, then posttest to the three groups to know the effectiveness of the exercise. In the wide push-up exercise group, there was an increase in strength by an average of 2.65 kg, power of 16.92 Joules, and endurance of 2.9 Times. In the narrow push-up exercise group obtained the results of an increase of 3.65 Kg of power, power of 27.91 Joule, and endurance of 3.65 Times. While in the control group obtained the results of an increase of 0.75 Kg of power, power of 4.39 Joule, and endurance of 0.85 Times.Based on the results of research and discussion as described in the previous chapters, it can be concluded that there is a significant influence on the wide push-up exercises on the increase of strength, power, and endurance, there is a significant influence on the exercise of narrow push-up against increased power, power, and endurance, and there are significant differences in influence between wide push-up and narrow push-up exercises for increased strength, power, and endurance Keywords: Wide push-up exercise, narrow push-up, strength, power, endurance